Amino-functionalized alginate/graphene double-network hydrogel beads for emerging contaminant removal from aqueous solution. (February 2020) - Sun, Yiran; Zhou, Tao; Li, Weiying; Yu, Fei; Ma, Jie
Abstract: Inorganic-organic composite hydrogels have attracted much attention in recent years. In this study, an amino-functionalized graphene/alginate double-network hydrogel (NH2 -DN) with excellent mechanical and adsorption properties was successfully prepared. Triethylenetetramine (TETA) was used as a crosslinker which promotes random few-layer graphene sheets stacking and resulted in a reduced graphene oxide (rGO) network, containing mesopore and macropore structures on the hydrogel surface. Compared to single network hydrogel, enhanced thermal stability and mechanical properties were achieved in NH2 -DN. The elasticity modulus was improved by approximately 3 times due to the formation of the double-network. More importantly, NH2 -DN exhibited excellent adsorption properties for typical emerging contaminants (Cu 2+ and ciprofloxacin (CIP)). Compared with that of an ordinary graphene/alginate single-network hydrogel (SN), the adsorption capacity of the NH2 -DN for Cu 2+ and CIP reached 153.91 mg g −1 and 301.36 mg g −1, respectively, which was increased by 130% and 182%, respectively. Adsorption isotherm and kinetic analyses reveal that the adsorption process of CIP onto the NH2 -DN was dominated by chemical affinity. Adsorption properties were comprehensively examined, including the effects of the solid-liquid ratios, pH, and ionic strength. NH2 -DN retained 94% of its adsorption capacity when the ionic strength was 0.5 mol L −1 and maintained at least 87% of its adsorption capacity in weak acidic and alkaline solutions. This novel amino-functionalized organic-inorganic hydrogel has great potential in environmental applications owing to its outstanding physicochemical, mechanical, and adsorption properties for emerging contaminants in wastewater. Graphical abstract: The novel amino functionalized graphene/Alginate double network hydrogel could be potentially applied in the removal of emerging contaminates in wastewater by π–π EDA interaction, hydrogen bonding and electrostatic interaction, owing to its outstanding physicochemical, mechanical and adsorption properties. Image 1 Highlights: Amino-functionalized graphene/alginate double-network hydrogel was prepared. Mechanical strength and thermal stability of NH2 -DN was significantly improved. NH2 -DN exhibited excellent adsorption property (Cu 2+ : 153.91, CIP: 301.36 mg/g).